the Effect of sun breakers characteristics on wind noise - Miqdad Haider Al-Jawadi; Samar hilal Askar (Iraqi Journal of Architecture and Planning, 2018)
In hot regions like Iraq, where solar energy is very high, sun breaks are preferred to beimplemented in design of the buildings as apart of the facade. Some types of sun breakers causewhistling noise or other types of noise which annoy occupants of the building especially if thebuilding is residential.as it has been found, numbers of sun breakers may act similar in preventing sun raypenetration, therefore classified these shapes according to it's effects on causing noise may helpdesigners in choosing the shapes matching there esthetic needs with less noise generating.Thus sun breakers with different shapes has been studied in this research using cfdprogram to predict the noise which caused by each type of sun breakers using forced wind onthem in different directions.The results showed that's possible to provide designers with clearpicture on the behavior of sun breakers on noise generating in order to prevent the annoy ones.